ANALISIS PENGARUH PENAMBAHAN VOLUME DAN LAMA FERMENTASI TERHADAP KELISTRIKAN BIOBATERAI SARI BUAH NENAS (ANANAS COMOSUS) - Masthura Masthura; Nadilla Putri; Abdul Halim Daulay (Universitas Islam Negeri Alauddin Makassar, 2021)
The purpose of this research to analyze the effect of increasing the volume and fermentation time on the bio-battery electricity of pineapple juice. Bio-battery prototype design with acrylic size 12x5x7 consisting of 6 pair of Cu-Zn electrodes. The volume of solution used was 150 ml, 200 ml, and 250 ml. The pineapple juice solution was fermented for 3 days, 5 days, 7 days, 9 days, and 11 days. A pH meter is used to measure the acidity of the solution. Electrical measurements such as electric current and voltage with a digital multimeter. When the solution is fermented for 11 days, the maximum electrical value is obtained with a volume of 200 ml which was 4,84V; 14,58mA; and 70,57mW. In this study, increasing the volume of the solution did not have much effect on the electrical voltage. Pineapple juice bio-battery is used to turn on the red LED for 2 hours with a voltage drop of 0,01-0,04V. After reaction, the Copper was thickened due to the oxidation with the Zinc.